2009
DOI: 10.1089/apc.2009.0085
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Health Setting-Based Stigma Intervention in Five African Countries

Abstract: The study aim is to explore the results of an HIV stigma intervention in five African health care settings. A case study approach was used. The intervention consisted of bringing together a team of approximately 10 nurses and 10 people living with HIV or AIDS (PLHA) in each setting and facilitating a process in which they planned and implemented a stigma reduction intervention, involving both information giving and empowerment. Nurses (n ¼ 134) completed a demographic questionnaire, the HIV=AIDS Stigma Instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 23 publications
2
95
0
1
Order By: Relevance
“…Of the 19 studies reviewed, 14 reported a reduction in HIV stigma; however, only two of these studies were rigorously designed and had used valid and reliable tools to measure a reduction in HIV stigma. Stangl and colleagues (2013) systematically reviewed 48 studies completed during the previous 10 years; 11 interventions were conducted with HCP and, of those, three were with nurses (Pisal et al, 2007;Uys et al, 2009;Williams et al, 2006) and one with nursing students (Yiu, Mak, Ho, & Chui, 2010). Interventions included combinations of organized education courses and other informal learning methods, some coupled with opportunities to interact with PLWH.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of the 19 studies reviewed, 14 reported a reduction in HIV stigma; however, only two of these studies were rigorously designed and had used valid and reliable tools to measure a reduction in HIV stigma. Stangl and colleagues (2013) systematically reviewed 48 studies completed during the previous 10 years; 11 interventions were conducted with HCP and, of those, three were with nurses (Pisal et al, 2007;Uys et al, 2009;Williams et al, 2006) and one with nursing students (Yiu, Mak, Ho, & Chui, 2010). Interventions included combinations of organized education courses and other informal learning methods, some coupled with opportunities to interact with PLWH.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The intervention was adapted from the validated intervention manual of Uys et al (2009) and was based on three tenets, namely the a) sharing of information on HIV stigma and coping with HIV stigma, b) the equalising of relationships between PLWH and PLC through increased interaction and contact among them by grouping them together, and c) the empowerment of members of both groups towards leadership in HIV stigma reduction through practical knowledge and experience of project planning regarding HIV stigma reduction and implementation in their communities. The comprehensive community-based HIV stigma reduction intervention primarily involved three processes (see Fig.…”
Section: The Interventionmentioning
confidence: 99%
“…Similarly, Uys et al (2009) used three basic elements in their intervention, namely accurate information, personal contact with the stigmatised and skills to cope with stigma. Ongoing research started promoting multi-pronged approaches such as a combination of sharing information and building skills, or education and empowerment combined with personal contact (Brown et al, 2003;Holm-Hansen, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The authors recommended that future studies pay greater attention to internal validity to maximize the potential for statistical and public health significance. Four of the 11 HCP studies included in the Stangl and colleagues (2013) review were interventions conducted with nurses in China (Williams et al, 2006), India (Pisal et al, 2007), African countries (Uys et al, 2009), and with nursing students in Hong Kong (Yiu, Mak, Ho, & Chui, 2010). Most interventions included in the review combined information with skills building and contact with PLWH, and demonstrated a positive impact on HIV knowledge, infection control practices, and willingness to treat PLWH.…”
mentioning
confidence: 99%